Systemic phaeohyphomycosis in splitnose rockfish (Sebastes diploproa) caused by Devriesia sp. Issue 5 (27th January 2021) - Peel, Melanie J.; Adams, Lance; Stevens, Brittany; Garner, Michael M.; Maguire, Cheryl
Abstract: A novel pathogen was documented after two wild‐caught, juvenile, splitnose rockfish presented with buphthalmia, grey corneal endothelial plaques and evidence of uveitis. Cytologic evaluation of ocular contents revealed fungal hyphae. Histologic evaluation identified multiple fungal granulomas and granulomatous inflammation in the globes, periocular tissue and heart. Fungi were slender, hyphenated and branched at angles, had parallel cell walls and had brown pigmentation in haematoxylin‐ and eosin‐stained sections. Both fish were diagnosed with phaeohyphomycosis. Culture with nuclear ribosomal RNA internal transcribed spacer (ITS) segment identification further classified the fungus as Devriesia sp ., which has not been previously documented as a cause of disease in animals.